Personal characteristics and level of management as determinants of the conceptual skills of academic librarians in Quezon City - Peza, Judith O.; Yang, Jackson V. (Quezon City : Institute of Library and Information Science, University of the Philippines Diliman, 2003)
Management is very essential in every organization. In a library setting, management is one of the important factors that makes it function. Management has three levels, the top, middle and the low management wherein in each level, it has different functions. The top management should have greater conceptual skills in order for it to perceive the future of the library. The people in this level must have the ability to think beyond time to be able to make the library more effective. The middle level management should have the same quantity of conceptual skills and technical skills. On the other hand, the low management level should have greater technical skills because their job is mostly hands-on.
The design of this study used questionnaire survey to collect data investigating the relationship of the independent variables (age, educational attainment, length of work experience and level of management) and the conceptual skills. A total of thirty questionnaires with sixteen conceptual questions each that were distributed to the ten academic libraries in Quezon City and all of which were used in this study. The sample of the study consisted of thirty (30) respondents, twenty-nine (29) of which are female and the other one (1) is male.
Two instruments were selected for this study. The researcher used the Graduate Management Admissions Test (GMAT), 1996 as a critical reasoning test to proxy for a conceptual skills test. A substitute for a conceptual skills test was needed because the researcher was not able to find a test that corresponds to a conceptual skills test.
This research showed that the independent variables (age, educational attainment, length of work experience and level of management) do not affect the dependent variable (conceptual skills). This was shown using the One-Way Anova through the use of SPSS.
Vita.
Thesis (Bachelor of Library and Information Science)--University of the Philippines Diliman
Keywords: Academic libraries -- Administration -- Philippines -- Quezon City